2015
DOI: 10.1124/mol.114.097352
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of cAMP Response Element Binding Protein in Ginsenoside Rg1-Mediated Inhibition of Na+/Glucose Cotransporter 1 Gene Expression

Abstract: The Na 1 /glucose cotransporter 1 (SGLT1) is responsible for glucose uptake in intestinal epithelial cells. It has been shown that the intestinal SGLT1 level is significantly increased in diabetic individuals and positively correlated with the pathogenesis of diabetes. The development of targeted therapeutics that can reduce the intestinal SGLT1 expression level is, therefore, important. In this study, we showed that ginsenoside Rg1 effectively decreased intestinal glucose uptake through inhibition of SGLT1 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Individually, Re is known to exhibit potent antidiabetic effects (Attele et al 2002 ), Rc is antiadipogenic and Rb1 improves insulin signaling and fatty liver by activating AMPK (Shen et al 2013, Shen at al. 2015 and by down-regulating intestinal transport (Wang et al 2015), the effects similar to those observed in the present study.…”
Section: R a F Tsupporting
confidence: 90%
“…Individually, Re is known to exhibit potent antidiabetic effects (Attele et al 2002 ), Rc is antiadipogenic and Rb1 improves insulin signaling and fatty liver by activating AMPK (Shen et al 2013, Shen at al. 2015 and by down-regulating intestinal transport (Wang et al 2015), the effects similar to those observed in the present study.…”
Section: R a F Tsupporting
confidence: 90%
“…2). For example, binding of hepatic nuclear factor (HNF) 1, transcription factor SP1, and cAMP response element-binding protein (CREB) to the 5′ region of the human SGLT1 gene and their effects on transcription have been demonstrated [259,417]. Employing murine STC-1 cells derived from intestinal endocrine cells, data were obtained which suggest that glucose-induced upregulation of transcription of ovine SGLT1 is dependent on the integrity of the HNF-1 consensus sequence in the promotor [404].…”
Section: Regulation Of Sglt1mentioning
confidence: 99%
“…A recent clinical study reported that the glycated hemoglobin levels of oral SGLT1 inhibitors were lower than placebo in patients with type 1 diabetes who were receiving insulin (Garg et al, 2017 ). Ginsenoside Rg1, through the regulation of SGLT1 gene expression to effectively reduce intestinal glucose uptake, provides a potential strategy for antihyperglycemia and antidiabetic treatments (Wang et al, 2015a ). Ginsenoside Rg3, F2, compound K, and Rh2 can also inhibit SGLT1 (Gao et al, 2017a ).…”
Section: Effects On Glucose Transportmentioning
confidence: 99%
“…Many studies have reported the antidiabetic activity of ginsenosides. Ginsenosides may improve blood glucose through the regulation of glucose absorption (Shang et al, 2014 ), intervention in glucose transport and/or glucose disposal (Wang et al, 2015a ), and the alteration of insulin secretion and binding (Gu et al, 2013 ). As ginsenosides affect multiple metabolic pathways, their efficacy is complex; furthermore, the various ginsenoside monomer components are difficult to separate.…”
Section: Introductionmentioning
confidence: 99%